Pancasila Soekarno (Idiologi alternatif terhadap globalisasi dan Syari'at Islam ) - SAKSONO, Gatut (Rumah Belajar Yabinkas, 2007)
Pancasila Soekarno (Idiologi alternatif terhadap globalisasi dan Syari'at Islam)